Calculation of the γ-TiAl Lattice Resistance - Feng, R.C.; Li, L.L.; Li, H.Y.; Wang, Z.M.; Zhu, Z.X. (Проблемы прочности, 2019)
The dislocation width and lattice resistance (Peierls stress) of a γ-TiAl alloy are calculated by the density ratio method. The lattice resistance is shown to decrease with the dislocation width. The relationship between the Peierls stress and dislocation width variation is defined by theoretical derivation. The yield stress is negatively correlated with the shear stress of the material. It can become a useful tool for choosing an appropriate shear stress under deformation.